Jaringan Intelektual Dan Ideologi Pesantren Salafi Jihadi: Studi pada Daerah “Zona Merah” Terorisme di Bima - Malik, Abdul (Ta'allum: Jurnal Pendidikan Islam, 2018)
This article aims to investigate the relationship between Intellectual networks and ideological with the development of radicalism in the "Salafi Jihadi" pesantren. There are many typelogies in the pesantren that develop in the Bima Regency. Among them are Islamic boarding schools that are affiliated to the jihadi salafi group, such as the UBK pesantren. Intellectualnetworks and ideological allegedly contributed to the emergence of radical values ​​in the learning process in the pesantren. This study uses qualitative phenomenological methods, in which the researcher reveals data in accordance with the natural setting. While the data collection instruments used were in-depth interviews and all forms of observation. It was found in this study that intellectual networks are a network of knowledge that shapes the religious understanding of religious teachers in the pesantren. This network is formed through the scientific sanad of religious teachers at UBK pesantren with Islamic organizations outside the pesantren. This network is suspected as a container in supplying what is called values ​​or ideology. Ideology formation in a person is more influenced and determined by how strong the network that is closest to the individual is pushed.